Chronic electrical performance of a new ultra-thin left ventricular quadripolar pacing lead. (24th May 2021) - Anselme, F; Ziglio, F; Shan, N; Heckman, LIB; Kuiper, M; Prinzen, FW
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): H2020-FTI [Fast Track to Innovation] Pilot-2016 and MicroPort CRM Background: Left ventricular (LV) lead positioning is an important contributor to cardiac resynchronization therapy (CRT) response. Multiple additional LV sites could be stimulated by passing a new ultra-thin (1.2 Fr, 0.4 mm) quadripolar microlead from one LV vein into another via venous collaterals. Purpose: Study the acute and chronic stability and electrical pacing performance of a novel 1.2 Fr quadripolar microlead ("Axone 4LV"). Methods: Seven healthy adult dogs underwent CRT defibrillator implantation, including a right ventricular lead and the microlead. The microlead was advanced into the coronary sinus network using a dedicated microguide catheter. The animals were followed up at 1, 15, 30 and 90 days post-implant to evaluate chronic stability and electrical pacing performance. Results: Successful uncomplicated implantation was achieved in all cases. Despite the small diameter of the distal veins and collaterals, placement of the pacing electrodes in two different LV veins was feasible via available collateral passages. Lead position was stable in all cases and over the entire study period. Capture threshold and pacing impedance at 90 days post-implant were 1.7 ± 0.5 V with 1323 ± 245 Ω, respectively, at 0.5 ms pulse width. The mean pacing energy to get capture was 1.1 ± 0.5 µJ and less than 2 µJ in all cases (2 µJ ≈ 1.4 V @500 Ω, 0.5 ms). No phrenic nerve stimulation was observed during pacing. Conclusions: The novel 1.2 Fr quadripolar microlead demonstrated adequate stability and good electrical performance allied to low energy consumption. This quadripolar microlead may extend pacing options while increasing device longevity in CRT.